Roles for PI3K/AKT/PTEN Pathway in Cell Signaling of Nonalcoholic Fatty Liver Disease - Matsuda, Satoru (Hindawi Publishing Corporation, 2013)
Nonalcoholic fatty liver disease (NAFLD) is the most common form of liver pathologies and is associated with obesity and the metabolic syndrome, which represents a range of fatty liver diseases associated with an increased risk of type 2 diabetes. Molecular mechanisms underlying how to make transition from simple fatty liver to nonalcoholic steatohepatitis (NASH) are not well understood. However, accumulating evidence indicates that deregulation of the phosphatidylinositol 3-kinase (PI3K)/AKT pathway in hepatocytes is a common molecular event associated with metabolic dysfunctions including obesity, metabolic syndrome, and the NAFLD. A tumor suppressor PTEN negatively regulates the PI3K/AKT pathways through its lipid phosphatase activity. Molecular studies in the NAFLD support a key role for PTEN in hepatic insulin sensitivity and the development of steatosis, steatohepatitis, and fibrosis. We review recent studies on the features of the PTEN and the PI3K/AKT pathway and discuss the protein functions in the signaling pathways involved in the NAFLD. The molecular mechanisms contributing to the diseases are the subject of considerable investigation, as a better understanding of the pathogenesis will lead to novel therapies for a condition.